Wireless system identification for linear network - Asirvadam , Vijanth Sagayan (2009)
Wireless technologies have tend to become core element of system e.g. sensors and logging system. When there is an input to the system and output to predict thus identification represents an important tool in many practical engineering circumstances. The current trend is to integrate wireless technologies and system identification together in sense of having an identification element or identifier that is able to give a good description for the system dynamic when the system observations are sent to it wirelessly. The paper investigates the possibility of performing system identification over wireless network for online linear process system.